Requirement Model for Student Management System - Mathan, Balaraman (2005)
In any development project the aims at producing artifact, the main focus of both analysis and design activities are on models. To produce this model, the analyst must identify the user requirement. The requirement helps to understand the new needs and how to full fill or satisfied the user. Requirement model is one of the techniques used to model out the requirement. Requirement model is a model that gives a complete view of the requirement for the particular system. The purpose of this study is to create the requirement model for student management. System Modeling and prototyping was used to validate the requirement. The model must rich of meaning where the whole requirement model must be accurate, complete and instantly recognizable. The UML graphical notation was used to model out the requirement, mean while HOORA Analysis Tools was used to validate the requirement model. A set of requirement list will be produced in this study. In the end of this study the problem and limitation of the project and the recommendations for future research will be discuss.